Komunitas serangga hama padi rawa lebak yang ditanam dengan berbagai jarak tanam - Herlinda, Siti; Apryanti, Hesti; Susilawati, Susilawati; Anggraini, Erise (Perhimpunan Entomologi Indonesia, 2018)
Rice spacing can affect the species and populations of insect pests. The closer spacing of rice are suitable for the habitats and niches of insect pests. This research was aimed to observe the community of insect pest on rice planted with various spacing regime. Field experiment was carried out on a-15 hectare rice field grown using various rice spacing: